Ethical Aspects of Age estimation for Forensic purposes in Saudi Arabia - Alshamrani, Khalaf (Acta Bioethica, 2022)
In forensic and legal contexts, an assessment of skeletal maturation is required to predict the chronological age in certain circumstances in which the chronological age is undocumented or unable to be proven. Carrying such medical examinations will always pose an ethical concern, especially in cases of assessing sexual maturity as well as examinations involving ionizing radiation. The cultural and religious barriers are also discussed concerning the ethical standards set in Saudi Arabia. Several ethical issues concerning age estimation examinations including issues related to consent forms, privacy, and radiation hazards have been documented. While ethical issues regarding radiation hazards are more likely to be overcome by introducing other imaging modalities without radiation hazards, ethics related to consent forms and privacy are still to be improved.